2015
DOI: 10.3109/13880209.2015.1010737
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofHammada scopariaflavonoid-enriched fraction on liver injury induced by warm ischemia/reperfusion

Abstract: Context: Hepatic ischemia/reperfusion injury (IRI) is a major cause of liver damage during liver surgery and transplantation. Plants have historically been used in treating liver damage, and Hammada scoparia (Pomel) (Chenopodiaceae) has been reported to possess a broad spectrum of pharmacological and therapeutic activities. Objective: In this study, a flavonoid-enriched fraction was used before the warm ischemia (WI) process as pharmacological preconditioning and in combination with technical postconditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…6B). Corroborating this finding, the serum levels of AST, ALT, and LDH, which are strongly associated with the damage of hepatocytes [46][47][48] , were also significantly suppressed in the ISO group in comparison to the AW group (Fig. 2A-C).…”
Section: Discussionsupporting
confidence: 64%
“…6B). Corroborating this finding, the serum levels of AST, ALT, and LDH, which are strongly associated with the damage of hepatocytes [46][47][48] , were also significantly suppressed in the ISO group in comparison to the AW group (Fig. 2A-C).…”
Section: Discussionsupporting
confidence: 64%
“…Hammada scoparia is widely used in traditional medicine in North Africa (Table 2) to prevent many diseases, such as hepatitis, inflammation, and obesity (Ezzeddine et al, 2016). Several traditional applications have revealed that extracts of Hammada scoparia have anti-cancer and anti-diabetic properties (Bouaziz et al, 2016;Boulanouar et al, 2013;Hamza et al, 2019;Saidi et al, 2015;Taïbi et al, 2020). This species commonly treats diseases, such as decoction, infusion, or cataplasm.…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%